2022
DOI: 10.1111/imr.13124
|View full text |Cite
|
Sign up to set email alerts
|

B cells going viral in the CNS: Dynamics, complexities, and functions of B cells responding to viral encephalitis

Abstract: Summary A diverse number of DNA and RNA viruses have the potential to invade the central nervous system (CNS), causing inflammation and injury to cells that have a limited capacity for repair and regeneration. While rare, viral encephalitis in humans is often fatal and survivors commonly suffer from permanent neurological sequelae including seizures. Established treatment options are extremely limited, predominantly relying on vaccines, antivirals, or supportive care. Many viral CNS infections are characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 148 publications
1
4
0
Order By: Relevance
“…Therefore, accelerated and enhanced CD4 TFH cell differentiation was followed by increased B cell activation and GC responses. We further confirmed that GC structures were properly forming within CD6 KO cLNs at day 14PI, a time when GCs were easily discernable in WT cLNs, by examining the accumulation of GL7 + B cells within the cLN B cell follicle 20,35,36 (Figure 3D). Consistent with accelerated GC somatic hypermutation, mCoV-specific IgG antibodies with increased affinity for mCoV were selectively detected in CD6 KO sera at day 14PI (Figure 3E).…”
Section: Gc Differentiation Is Enhanced In Cd6 Kos During Infectionsupporting
confidence: 56%
See 3 more Smart Citations
“…Therefore, accelerated and enhanced CD4 TFH cell differentiation was followed by increased B cell activation and GC responses. We further confirmed that GC structures were properly forming within CD6 KO cLNs at day 14PI, a time when GCs were easily discernable in WT cLNs, by examining the accumulation of GL7 + B cells within the cLN B cell follicle 20,35,36 (Figure 3D). Consistent with accelerated GC somatic hypermutation, mCoV-specific IgG antibodies with increased affinity for mCoV were selectively detected in CD6 KO sera at day 14PI (Figure 3E).…”
Section: Gc Differentiation Is Enhanced In Cd6 Kos During Infectionsupporting
confidence: 56%
“…Importantly, the opposing functions of CD6 in CD4 T cell activation are not easily attributed to murine intrinsic factors, as the CD6 KO mice used herein were generated from the same colony and housed in the same facility as in the above mentioned autoimmune studies [15][16] . Unfortunately, further comparison between autoimmune and virus models is complicated by numerous factors; In the autoimmune encephalomyelitis and uveitis models T cell activation is dependent on immunization with self-peptide or antigen in adjuvant resulting in the induction of both Th1 and Th17 CD4 T cells 15,46 , whereas virus-specific T cells are activated by replicating virus and presentation of viral antigen generating an exclusive Th1 response [17][18][19][20] . These models also utilize distinct innate immune scavenging, pattern recognition receptors, and antigen presenting cells, all of which also contribute to the outcome of T cell activation [48][49][50] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another very timely review by Dr. Bergmann and colleagues highlights other pathogens that have the potential to inflict permanent CNS damage: DNA and RNA viruses 7. Although viral infections of the CNS are rare, treatment options are severely limited and often neurological sequelae are permanent and present a lifelong threat to hosts.…”
mentioning
confidence: 99%